Pengaruh Pengetahuan Produk dan Kepercayaan terhadap Sikap Loyalitas Peserta BPJS Kesehatan Daerah Istimewa Yogyakarta - Rifqi Suprapto (BBM (Buletin Bisnis & Manajemen), 2016)
Badan Penyelenggara Jaminan Sosial (BPJS) is an Indonesian institution of social security so that the existence of social security, financial risk faced by a person, whether it is because the productive age, get sick, have an accident, and even death, will be taken over by the agency that organizes social security. BPJS matters relating to their attitude of loyalty of consumers have an impact on compliance with every consumer to perform an obligation in the payment of dues and recommend BPJS as health insurance to others. The study was conducted to investigate the influenced product knowledge and trust to attitudinal loyalty BPJS Participants. The results obtained: there is the positive influence Product Knowledge and Trust to the Affective Commitment of Attitudinal Loyalty BPJS participants. This shows that there is a positive influence on the attitudinal loyalty from participant satisfaction.Keywords: Product Knowledge, Trust, Attitudinal Loyalty, Affective Commitment, and BPJS Participants